HUBUNGAN PROFIL SEL DARAH MERAH DENGAN SERVICE/CONCEPTION (S/C) SAPI PERANAKAN ONGOLE (PO) DAN SAPI SIMENTAL-PO (SIMPO) DI YOGYAKARTA - , FAUZI, drh. Erif Maha Nugraha Setyawan, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Red blood cell profile researches of Ongole-Cross Breed Cattle (PO) and SimentalOngole-Cross Breed Cattle (SIMPO) which related to service per conception is infrequently taken in Indonesia. Considering the number of Ongole- Cross Breed Cattle and SimentalOngole-Cross Breed Cattle are many found in society thatâs why this research was be required. The aim of this research is to find out the blood imaging of Ongole-Cross Breed Cattle (PO) and Simmental Ongole-Cross breed Cattle (SIMPO) which related to reproduction system of Ongole-Cross breed Cattle (PO) which better than Simmental Ongole-Cross breed Cattle (SIMPO). Eighteen blood samples were collected in this research, 11 samples were from Ongole-Cross Breed Cattle and 7 samples were from Simental Ongole-Cross breed Cattle. The blood samples were delivered to The Integrated Research and Examination Laboratory of Gadjah Mada University (LPPT UGM). The parameter which was observed was the number of erythrosytes, hemoglobin values, PCV (Packed Cell Volume), MCV, MCH, MCHC. The result showed the erytrocytes average of Ongole-Cross Breed Cattle was 6,70 106/Î¼L, hemoglobin values 10,93 g/dL, and PCV 32,22%, MCV 48,19 fl, MCH 16.35 pg, MCHC 33,94 g/dL. The erythrosytes average of SimentalOngole- Cross Breed Cattle was 5,59 106/Î¼L, hemoglobin 9,51 g/dL, and PCV 27,18%, MCV 48,88 fl, MCH 17,12 pg, MCHC 32,62 g/dL. by comparing the measurement result and literature, so that, thesummarize is the result of the observation is still in normal range of cattle bloodâs image internationally. However, based on the statistical analysis, showed that the Ongole-Cross Breed Cattle has the higher red-blood count, hemoglobin concentrate, and PCV than SimentalOngole-Cross Breed Catle (P<0,05). Keyword: Ongole-Cross Breed Cattle, SimentalOngole-Cross Breed Cattle, Cow, red blood cell imaging.